Electrolytic capacitor

By using aluminum and aluminum alloy powder sintered bodies as electrode foils and combining specific electrolytes and separators designs, the problems of existing electrolytic capacitors reducing the capacitance and environmental pollution at high frequencies are solved, and a high capacitance and environmentally friendly electrolytic capacitor is achieved.

CN119560313APending Publication Date: 2025-03-04路碧康株式会社 +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411578961.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2022-07-05
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing electrolytic capacitors have reduced electrostatic capacity at high frequencies, and the etching process leads to an increase in environmental load, making it difficult to meet high capacity and environmentally friendly needs.

Method used

A sintered body composed of aluminum and aluminum alloy powder is used as the electrode foil, and a specific electrolyte solution and separator design is combined to form an electrolytic capacitor with high electrostatic capacity, avoiding the etching of the electrode material.

Benefits of technology

It achieves a higher electrostatic capacity than the traditional etching method, reduces environmental pollution, and has excellent electrostatic capacity at high frequencies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560313A_ABST
    Figure CN119560313A_ABST
Patent Text Reader

Abstract

The invention relates to an electrolytic capacitor. The present invention addresses the problem of providing an electrolytic capacitor that does not require an etching process for an electrode material and that can achieve a higher capacitance than an electrolytic capacitor that uses a conventional electrode foil in which the surface area is increased only by etching. As a solution, this electrolytic capacitor (10) is characterized by being provided with a capacitor element (1) having an anode foil (20), a cathode foil (23), and separators (24, 25) interposed between the anode foil (20) and the cathode foil (23), and an electrolyte solution impregnated into the capacitor element (1), the positive electrode foil (20) or the negative electrode foil (23) has a sintered body comprising sintered particles containing a powder of at least one of aluminum and an aluminum alloy.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with a filing date of July 5, 2022, an application number of 202280008571.2, and an invention name of electrolytic capacitor. Technical Field

[0002] The present invention relates to electrolytic capacitors. Background Art

[0003] Electrolytic capacitors are small, have large capacity, and are inexpensive, and are widely used as one of the important components of electronic equipment, electrical equipment, vehicle-mounted equipment, and the like.

[0004] Conventional electrolytic capacitors, such as the most widely used aluminum electrolytic capacitors, can be manufactured as follows: After chemically or electrochemically etching a high-purity aluminum foil to increase its surface area, an anode foil having a film formed on the surface of the aluminum foil by anodic oxidation and a cathode foil having an etched surface are used to manufacture it. Then, the obtained anode foil and cathode foil are arranged opposite to each other, and a separator is further sandwiched between these foils and wound to form an element of the structure, and the electrolyte is impregnated into the element of the structure. The element impregnated with the electrolyte is housed in a housing and sealed with an elastic sealing body to complete the electrolytic capacitor.

[0005] The high capacity of electrolytic capacitors is an important market demand directly related to the miniaturization of the mounted devices, and the high capacity is gradually realized based on the increase of etching rate. However, there is a theoretical limit to the increase of surface area based on etching, and it is gradually becoming unable to meet the increasing demand for high capacity year by year. In addition, in order to reduce the environmental load caused by hydrochloric acid containing sulfuric acid, phosphoric acid, nitric acid, etc. used in etching, it is also expected to replace the surface area increase method of etching foil.

[0006] Here, as a method of increasing the surface area instead of etching the foil, a capacitor using a metal sintered body as an anode has been proposed (Patent Document 1: Japanese Utility Model Application Laid-Open No. 59-140430).

[0007] However, a capacitor of this shape has a long distance from the anode to the cathode current collector, so the resistance component through the electrolyte becomes large, and there is a disadvantage that the electrostatic capacitance at high frequencies decreases.

[0008] As another method for increasing the surface area, an aluminum electrolytic capacitor has been proposed, which is characterized by using a foil having fine aluminum powder attached to the surface of the electrode foil (Patent Document 2: Japanese Patent Application Laid-Open No. 2-267916, and Patent Document 3: Japanese Patent Application Laid-Open No. 2006-108159).

[0009] However, the aluminum powder of the electrode foil disclosed in these documents has a small particle size, so there are the following disadvantages when forming an anodic oxide coating: there is sometimes a concern that the gaps between the sintered particles will be filled and the electrostatic capacitance will be reduced. In addition, when using an electrolyte for medium and high voltage capacitors with a high viscosity and resistivity, the electrostatic capacitance at high frequencies is reduced.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Utility Model Publication No. 59-140430

[0013] Patent Document 2: Japanese Patent Application Laid-Open No. 2-267916

[0014] Patent Document 3: Japanese Patent Application Publication No. 2006-108159 Summary of the invention

[0015] Problem that the invention aims to solve

[0016] The present invention is made in view of the above-mentioned needs for higher capacity and reduced environmental load, and its purpose is to provide an electrolytic capacitor that does not require etching of electrode materials and can achieve a higher electrostatic capacitance than conventional electrolytic capacitors using electrode foil whose surface area is increased only by etching.

[0017] Solutions for solving problems

[0018] The electrolytic capacitor of the present invention is characterized in that it comprises a capacitor element and an electrolyte, wherein the capacitor element comprises: an anode foil, a cathode foil and a separator sandwiched between the anode foil and the cathode foil, the electrolyte is impregnated in the capacitor element, and the anode foil or the cathode foil comprises: a sintered body composed of sintered particles containing powder of at least one of aluminum and an aluminum alloy.

[0019] The anode foil or the cathode foil preferably comprises the sintered body and a substrate for supporting the sintered body. In addition, the resistivity of the electrolyte is preferably 1500 Ω·cm or less, and the average particle size (D50) of the powder or the sintered particles is preferably 6 μm or less.

[0020] In addition, the aforementioned electrolyte solution is suitable for containing: a solvent including an organic solvent, or a solvent including a mixture of water and an organic solvent; and at least one electrolyte selected from the group consisting of an organic acid or an organic acid salt, an inorganic acid or an inorganic acid salt, and a mixture of an organic acid or an organic acid salt and an inorganic acid or an inorganic acid salt.

[0021] Effects of the Invention

[0022] According to the electrolytic capacitor of the present invention, the surface area of ​​the electrode foil is larger than the pit area of ​​the conventional etched foil, so a large electrostatic capacitance can be achieved. In addition, etching of the electrode foil is not necessarily required, resulting in a reduction in environmental load. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic cross-sectional view showing an example of the electrolytic capacitor according to the present embodiment.

[0024] Figure 2 This is an explanatory diagram for explaining an example of the capacitor element according to the present embodiment.

[0025] Figure 3 Graph showing the leakage current values ​​of the electrolytic capacitors of Example 13 and Example 14 in the high temperature load test. DETAILED DESCRIPTION

[0026] Hereinafter, preferred embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0027] Figure 1 2 is a cross-sectional view schematically showing the overall structure of the electrolytic capacitor 10 according to the present embodiment. Figure 2 2 is an explanatory diagram of the capacitor element 1 .

[0028] The electrolytic capacitor 10 of this embodiment is constructed as follows: a capacitor element 1 is arranged inside a bottomed cylindrical outer casing 4 formed of a metal such as aluminum, and the opening of the outer casing 4 is sealed by a sealing body 3, and the sealing body 3 is fixed by fitting the opening edge (curl 14), thereby forming the structure.

[0029] In addition, the capacitor element 1 of the present embodiment is a wound capacitor element 1 composed of an anode foil 20 having a sintered body 22 of aluminum powder formed on the surface of a core material (substrate) 21, a cathode foil 23, a first separator 24 arranged between the anode foil 20 and the cathode foil 23, and a second separator 25, and is sealed in an exterior casing 4 after being impregnated with an electrolyte. It should be noted that reference numeral 2 denotes a lead 2 connected to the anode foil 20 and the cathode foil 23, respectively. Each lead 2 has a connection portion with the anode foil 20 or the cathode foil 23, namely, a lead tab 5 and a terminal 6. However, the form of the electrolytic capacitor 10 of the present invention is not limited, except Figure 1 In addition to the winding type shown in the figure, for example, a stacked type, a coin type, etc. can also be used. In addition, the form of the terminal part (the entire part connected to the electrode foil 20, 23 exposed outside the electrolytic capacitor 10) is also not limited. Figure 1 In addition to the lead shape shown, it may be, for example, a substrate-based self-supporting shape, a screw terminal shape, etc. Therefore, the shape, number, and connection form of the members constituting the terminal portion are not limited.

[0030] As an example, in a substrate-free electrolytic capacitor (not shown) in which the terminal 6 is vertically arranged on a substrate formed by a two-layer sealing body 3, the connection portion with the electrode foils 20 and 23, namely the lead tabs 5, is connected to multiple locations in each electrode foil 20 and 23. This structure can be understood as a structure in which multiple lead tabs 5 are provided, and can be understood as a structure in which the lead tabs 5 are branched at the end. According to this structure, compared with a structure in which each electrode foil 20 and 23 is connected to one (one location) lead tab 5, the metal resistance and inductance of each electrode foil 20 and 23 can be reduced, and the low impedance of the electrolytic capacitor and the improvement of the allowable pulsating current can be achieved. In addition, the lead tabs 5 connected to multiple locations of the electrode foils 20 and 23 are assembled and fixed to the terminal 6 and the sealing body 3, so that the stability of the capacitor element 1 is improved, and the vibration resistance of the electrolytic capacitor can be improved.

[0031] In addition, the sintered body 22 of aluminum powder in the present embodiment is formed on both sides or one side of the substrate 21. The substrate 21 may not necessarily be included, and the electrode foil (anode foil 20) may be formed only by the sintered body 22 of aluminum powder. In this way, regardless of the presence or absence of the substrate 21, the electrode foil (here, the anode foil 20) whose surface is formed by the sintered body 22 is referred to as "sintered body foil" in this application. In the electrolytic capacitor 10 of the present embodiment, the anode foil 20 is composed of a sintered body foil and the cathode foil 23 is composed of an etched foil, but the electrolytic capacitor 10 of the present invention only needs to have at least one of the two electrode foils (anode foil 20 and cathode foil 23) The electrode foil (anode foil 20 or cathode foil 23) is composed of a sintered body foil. For example, both the anode foil 20 and the cathode foil 23 can be composed of sintered body foil.

[0032] According to the present embodiment, the electrode foil (anode foil 20) has a surface area greater than the pit area of ​​the conventional etched foil, and therefore, a large electrostatic capacitance can be achieved. In addition, for the aluminum sintered body capacitor proposed in the past (e.g., Patent Document 1), the present embodiment is a structure in which the sintered body 22 is formed into a foil shape and wound, so that the distance between the anode and cathode collectors becomes closer, thereby reducing the resistance component across the electrolyte, and the electrostatic capacitance at high frequencies (about 10kHz) is excellent. In addition, for electrolytic capacitors using foils with fine aluminum powder attached (e.g., Patent Documents 2 or 3), the electrostatic capacitance at high frequencies (about 10kHz) of the present embodiment is also excellent.

[0033] Here, the powder sintered body 22 refers to a sintered body composed of sintered particles of the powder. The sintered particles refer to sintered particles (referred to as "sintered particles" in the present application) obtained by sintering particles of the powder (referred to as "powder particles" in the present application).

[0034] The sintered body 22 of the aluminum powder of the present embodiment is composed of sintered particles of powder containing at least one of aluminum and aluminum alloy. For the aluminum in the aluminum and aluminum alloy, from the viewpoint of preventing adverse conditions caused by impurities, the aluminum purity is preferably 99.8% by weight or more, and in particular, in order to suppress the increase of leakage current under high temperature load, the aluminum purity is more preferably 99.99% by weight or more. In addition, in the case of aluminum alloy, for example, an alloy containing one or more elements such as silicon (Si), iron (Fe), copper (Cu), manganese (Mn), magnesium (Mg), chromium (Cr), zinc (Zn), titanium (Ti), vanadium (V), gallium (Ga), nickel (Ni), boron (B) and zirconium (Zr) can be used. In this case, the content of these elements is preferably set to 100 ppm by weight or less, and particularly preferably set to 50 ppm by weight or less.

[0035] The sintered body 22 is formed by sintering sintered particles of powder of at least one of aluminum and aluminum alloy while maintaining pores with each other. That is, the sintered particles are connected with each other while maintaining pores, and have a three-dimensional network structure. By forming such a porous sintered body, the desired electrostatic capacitance can be obtained even without etching. The porosity of the sintered body 22 can be appropriately set within a range of generally more than 10% according to the desired electrostatic capacitance, etc. In addition, the porosity can be controlled, for example, according to the particle size of the powder of aluminum or aluminum alloy of the starting material, the composition of the paste composition containing the powder (resin binder), etc.

[0036] The shape of the sintered body 22 is not particularly limited, but in the case of a configuration including the substrate 21, it is usually in the form of a foil having an average thickness on one side of preferably 5 μm or more and 100 μm or less, particularly preferably 5 μm or more and 60 μm or less. The average thickness can be calculated by observing a cross section of the sintered body foil with a scanning electron microscope (SEM) or the like, measuring the thickness at any 10 points, and averaging the measured values.

[0037] It should be noted that the average particle size of the sintered particles is preferably 80 μm or less. If the average particle size is larger than 80 μm, a desired electrostatic capacitance may not be obtained.

[0038] The average particle size of the sintered particles is preferably 1 μm or more. If the average particle size is less than 1 μm, there is a concern that the desired withstand voltage cannot be obtained. It should be noted that a small average particle size is advantageous when the surface area is increased, but if the average particle size is excessively reduced, there is a concern that the electrostatic capacitance may be reduced by filling the gaps between the sintered particles when an anodic oxide film is formed as required. From the perspective of preventing such a reduction in electrostatic capacitance, it is more preferred to have an average particle size of 2.5 μm or more.

[0039] From the viewpoint of improving the electrostatic capacitance characteristics at around 10 kHz, the average particle size is particularly preferably 2.5 μm or more and 6 μm or less.

[0040] The substrate 21 is not particularly limited, and aluminum foil can be preferably used. The substrate 21 may be used without being subjected to etching treatment, but may be subjected to etching treatment as necessary.

[0041] Aluminum or aluminum alloy having the same composition as the aluminum or aluminum alloy powder can be used as the aluminum foil of the substrate 21. In order to suppress the increase of leakage current under high temperature load, the aluminum purity is more preferably 99.99 wt % or more.

[0042] The thickness of the aluminum foil as the substrate 21 is not particularly limited, but is preferably within a range of 5 μm to 100 μm, and particularly preferably within a range of 5 μm to 60 μm.

[0043] The method of forming the sintered body 22 on the substrate 21 to produce the electrode foil 20 ( 23 ) is based on the following method.

[0044] That is, it includes the following steps:

[0045] 1. A first step of forming a coating formed of a composition containing a powder of at least one of aluminum and an aluminum alloy on a substrate 21; and,

[0046] 2. A second step of sintering the film at a temperature of 560°C to 660°C.

[0047] Step 1

[0048] In the first step, a coating film made of a composition including powder of at least one of aluminum and an aluminum alloy is formed on the substrate 21 .

[0049] As the composition and ingredients of aluminum or aluminum alloy, those described above can be used.

[0050] The particle shape of the powder, i.e., powder particles, is not particularly limited, and spherical, amorphous, flaky, or other shaped powder particles can be suitably used. Spherical powder particles can be particularly suitably used.

[0051] The average particle size of the powder, i.e., the powder particles, is preferably 80 μm or less. If the average particle size is larger than 80 μm, the desired electrostatic capacitance may not be obtained.

[0052] The average particle size of the aforementioned powder, i.e., the powder particles, is preferably 1 μm or more. If the average particle size is less than 1 μm, there is a concern that the desired withstand voltage cannot be obtained. It should be noted that when the surface area is increased, a small average particle size is advantageous, but if the average particle size is excessively reduced, there is a concern that the electrostatic capacitance will decrease due to the gaps between the sintered particles being filled when the anodized film is formed as required. From the perspective of preventing such a decrease in electrostatic capacitance, it is more preferable to make the average particle size 2.5 μm or more.

[0053] From the viewpoint of improving the electrostatic capacitance characteristics at around 10 kHz, the average particle size is particularly preferably 2.5 μm or more and 6 μm or less.

[0054] It should be noted that the particle size of the powder particles does not change significantly even after the sintering in the second step, and the average particle size of the sintered particles can be adjusted to the same level by adjusting the average particle size of the powder particles.

[0055] The aforementioned composition may include a resin binder, a solvent (solvent), a sintering aid, a surfactant, etc. as required. They may all use known or commercially available ones. It is particularly preferred to contain at least one of a resin binder and a solvent and use it as a paste-like composition. Thus, a coating can be formed efficiently.

[0056] In addition, a known solvent can be used. For example, in addition to water, organic solvents such as ethanol, toluene, ketones, and esters can be used.

[0057] Step 2

[0058] In the second step, the film is sintered at a temperature of 560° C. or higher and 660° C. or lower.

[0059] The sintering temperature is 560° C. to 660° C., preferably 560° C. to less than 660° C., more preferably 570° C. to 659° C. The sintering time varies depending on the sintering temperature, etc., but can be appropriately determined in the range of about 5 to 24 hours.

[0060] The sintering atmosphere is not particularly limited, and may be, for example, a vacuum atmosphere, an inert gas atmosphere, an oxidizing gas atmosphere (including an atmospheric atmosphere), a reducing atmosphere, etc., but it is particularly preferred to be a vacuum atmosphere or a reducing atmosphere. In addition, regarding the pressure conditions, it may also be normal pressure (atmospheric pressure), reduced pressure, or pressurized.

[0061] It should be noted that, when the aforementioned composition contains organic components such as a resin binder, it is preferred that after the first step and before the second step, a heat treatment (degreasing treatment) is performed in advance within a temperature range of 100° C. to 600° C. for a holding time of more than 5 hours. The heat treatment atmosphere is not particularly limited, and for example, a vacuum atmosphere, an inert gas atmosphere, or an oxidizing gas atmosphere, etc., are all acceptable. In addition, the pressure condition may also be normal pressure (atmospheric pressure), reduced pressure, or pressurized.

[0062] The electrode material of the present invention can be obtained through the aforementioned second step. It can be used as an electrode (electrode foil 20 (23)) for the aluminum electrolytic capacitor 10 without being subjected to etching treatment, but it can also be subjected to etching treatment as needed. When used as the electrode foil 20 (23), the aforementioned electrode material is cut into components of appropriate size after the second step, or after the third step when the third step is performed.

[0063] Step 3

[0064] The electrode material may be subjected to chemical conversion treatment as a third step as needed to form a chemical conversion film (oxide film). For example, a dielectric with withstand voltage, i.e., an oxide film, may be formed by a predetermined anodic oxidation treatment to form anode foil 20 for electrolytic capacitor 10 having a desired withstand voltage.

[0065] On the other hand, the electrode material after the second or third step can be used as the cathode foil 23, but the cathode foil 23 of the present embodiment is constituted by an etched foil using aluminum foil or aluminum alloy foil as the electrode material and the electrode material being etched. In the case of the aluminum alloy foil, for example, an aluminum alloy foil containing one or more elements such as silicon (Si), iron (Fe), copper (Cu), manganese (Mn), magnesium (Mg), chromium (Cr), zinc (Zn), titanium (Ti), vanadium (V), gallium (Ga), nickel (Ni), boron (B) and zirconium (Zr) in a total content of 1% by weight or less can be used. In particular, for example, the aluminum alloy foil containing copper is etched by chemical etching, so the cathode foil 23 can be manufactured at a relatively low cost.

[0066] The cathode foil 23, which is an etched foil, is usually not subjected to chemical conversion treatment, but instead forms a natural oxide film, or chemical conversion (formation of an oxide film) is performed by the use of the electrolytic capacitor 10 (e.g., repeated charging and discharging). Therefore, in particular, for the purpose of suppressing the progress of chemical conversion during charging and discharging, the cathode foil 23 may be subjected to chemical conversion treatment in advance to form a chemical conversion film (oxide film). Thus, even in the case of repeated charging and discharging, the progress of chemical conversion of the cathode foil 23 may be suppressed. The chemical conversion voltage of the chemical conversion cathode foil 23 is preferably set within the range of 2V to 6V.

[0067] In addition, as in the present embodiment, when at least one of the electrode foils (in the present embodiment, the anode foil 20) is composed of a sintered body foil, it is preferred that the other electrode foil (in the present embodiment, the cathode foil 23) is also set to a larger foil capacity according to the sintered body foil having a larger foil capacity. Assuming that in the present embodiment, the foil capacity of the cathode foil 23 (etched foil) is very small compared to the foil capacity of the anode foil 20 (sintered body foil), if the charge and discharge of the electrolytic capacitor 10 are repeated, the neutralization of the charge between the electrode foils 20 and 23 during discharge becomes insufficient, and a potential difference is generated between the cathode foil 23 and the electrolyte due to the charge, and the chemical conversion of the cathode foil 23 proceeds. As a result, the foil capacity of the cathode foil 23 decreases, and the electrostatic capacitance of the electrolytic capacitor 10 gradually decreases. From the viewpoint of preventing the deterioration of such an electrolytic capacitor 10, when one of the electrode foils is composed of a sintered body foil, the foil capacity of the other electrode foil is preferably set to 30μF / cm 2 More preferably 80μF / cm 2 More preferably, 100 μF / cm 2 It should be noted that the foil capacitance here refers to the electrostatic capacitance of the foil measured in accordance with the JEITA standard of the Japan Electronics and Information Technology Industries Association (formerly the Electronic Industries Association of Japan): EIAJ RC-2364A "Test Method for Electrode Peeling for Aluminum Electrolytic Capacitors" (revised in March 1999) (https: / / www.jeita.or.jp / japanese / standard / book / RC-2364A / #target / page_no=1).

[0068] It should be noted that the cathode foil 23 of the present embodiment may be formed of a titanium vapor-deposited foil or the like in which titanium is vapor-deposited on an aluminum foil or an aluminum alloy foil as the substrate 21, in addition to an etched foil or a sintered body foil. The titanium vapor-deposited foil has a larger foil capacity than an etched foil, and therefore, sufficient foil capacity can be ensured for the cathode foil 23.

[0069] Next, the electrolytic solution will be described.

[0070] In the present invention, the resistivity of the electrolyte is preferably 1500Ω·cm or less. As a result, the ratio of the electrostatic capacitance at 10kHz to the electrostatic capacitance at 120Hz becomes closer to 1 than before, and good electrostatic capacitance characteristics are obtained in a wide frequency range. In addition, from the perspective of ensuring the desired withstand voltage, the resistivity of the electrolyte is preferably 100Ω·cm or more.

[0071] The electrolyte of the present invention contains at least an electrolyte and a solvent. In addition, additives described below may also be added. As a solvent for dissolving the electrolyte and the additive, an organic solvent may be used alone, or a solvent of a water-organic solvent system, i.e. a mixture of an organic solvent and water may be used.

[0072] As an organic solvent, a protic solvent or an aprotic solvent can be used alone or by mixing two or more thereof. As required, one or more protic solvents can be used in any combination with one or more aprotic solvents. As a suitable protic solvent, for example, an alcohol compound can be cited. As a specific example of an alcohol compound that can be advantageously used here, it is not particularly limited, and the following can be cited, methanol, ethanol, propanol, butanol and other monohydric alcohols, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,4-butanediol, 1,3-butanediol and other dihydric alcohols (glycols), trihydric alcohols such as glycerol, or their derivatives, etc. In addition, suitable aprotic solvents are not particularly limited, and examples thereof include lactone compounds such as γ-butyrolactone, γ-valerolactone, δ-valerolactone, sulfolane, methylsulfolane, dimethylsulfolane, propylene carbonate, butylene carbonate, isobutylene carbonate, methylpyrrolidone, imidazolidinone, pyrrolidinenitrile, pyrrolidone, methylpyrrolidone, tetrahydrofuran, acetonitrile, N-methylformamide, N,N-dimethylformamide, nitrobenzene, their derivatives, and other intramolecular polar compounds.

[0073] In the electrolyte solution related to the present embodiment, as described above, a water-organic solvent system may be used instead of using an organic solvent alone. By using such a water-organic solvent system, the freezing point of the solvent can be lowered. As a result, the resistivity characteristics of the electrolyte solution at low temperatures are improved, and good low-temperature characteristics can be achieved, which are shown by a small difference in resistivity between low temperatures and normal temperatures.

[0074] When describing in further detail, if ethylene glycol is used as an organic solvent, the boiling point of this proton-based organic solvent is 198°C and the melting point is about -13°C. The temperature range required for capacitors is generally -40°C to 105°C, so the electrolyte using this solvent has a margin of characteristics at high temperatures, but at low temperatures, there is a concern that the electrical characteristics may be reduced due to the increase in viscosity and solidification of the electrolyte.

[0075] Therefore, the electrolyte of the present embodiment is used alone or mixed with a plurality of organic solvents having excellent temperature characteristics. On the other hand, when an organic solvent with a high freezing point is used, a water-organic solvent system is used by adding water, so that the freezing point of the solvent can be lowered to ensure the electrical characteristics at low temperatures. The electrolyte solubility and ion mobility of the water-organic solvent system electrolyte are very large, so a relatively low resistivity can be achieved compared to an electrolyte with an organic solvent alone. In addition, at low temperatures, the characteristics of the solvent are improved, so that an electrolyte having a breakthrough characteristic of a small difference in resistivity at low temperatures and at room temperature is obtained. Therefore, the electrolytic capacitor 10 using this electrolyte can certainly reflect the characteristics of the electrolyte and has good temperature characteristics.

[0076] The amount of water added to the water-organic solvent is preferably in the range of 0.1 mass % to 20 mass % of the total mass of the electrolyte. Thus, the above-mentioned low resistivity and good oxide film repair properties can be achieved, and water molecules are used to repair the oxide films of the electrode foils 20 and 23, which can exert relatively excellent oxide film repair properties.

[0077] In addition, as electrolyte, use organic acid, preferably carboxylic acid or its salt, dicarboxylic acid or hydroxycarboxylic acid boron complex or its salt, and use inorganic acid or its salt. These electrolyte components can be used alone, and can also be used in any combination of two or more electrolyte components. If carboxylic acid or its salt, dicarboxylic acid or hydroxycarboxylic acid boron complex or its salt and inorganic acid or its salt are used as electrolyte components, then it is expected that the freezing point of the electrolyte is reduced, therefore, it is possible to contribute to the further improvement of the low temperature characteristics of the electrolyte.

[0078] Examples of carboxylic acids that can be used as electrolyte components are not limited to those listed below, but include monocarboxylic acids represented by formic acid, acetic acid, propionic acid, butyric acid, p-nitrobenzoic acid, salicylic acid, benzoic acid, methylbenzoic acid, ethylbenzoic acid, isobutylbenzoic acid, sec-butylbenzoic acid, tert-butylbenzoic acid, etc. or their derivatives, and dicarboxylic acids represented by oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid, maleic acid, phthalic acid, azelaic acid, sebacic acid, octanoic acid, 1,6-decanedicarboxylic acid, 5,6-decanedicarboxylic acid, methyladipic acid, ethyladipic acid, isobutyladipic acid, sec-butyladipic acid, tert-butyladipic acid, 2-methylnonanediacid, 3-tert-butylhexanediacid, undecanedicarboxylic acid, octadecenedicarboxylic acid, 12-vinyl-8-octadecenedicarboxylic acid, dimethyloctadecadienetetracarboxylic acid, etc. or their derivatives. Alternatively, a carboxylic acid containing a hydroxyl group or the like such as citric acid may be used.

[0079] Moreover, the dicarboxylic acids or hydroxycarboxylic acids in the boron complexes of dicarboxylic acids or hydroxycarboxylic acids that can be used as the same electrolyte components should not be limited to those listed below, but examples include boron dioxalic acid, boron dimalonic acid, boron disuccinic acid, boron diadipic acid, boron dimaleic acid, boron diglycolic acid, boron dilactic acid, boron dimalic acid, boron ditartaric acid, boron dicitric acid, boron disalicylic acid, boron diphthalic acid, boron di(2-hydroxy)isobutyric acid, boron dimandelic acid, boron di(3-hydroxy)propionic acid, etc.

[0080] And then, as the example of the inorganic acid that can be used as identical electrolyte component, be not limited to the following enumerator, but can enumerate phosphoric acid, phosphorous acid, phosphonic acid, hypophosphorous acid, phosphinic acid, alkyl phosphoric acid, phosphomolybdic acid, boric acid, sulfamic acid etc.In addition, also can use the derivative of this inorganic acid as required.

[0081] Furthermore, as the salt of the above-mentioned carboxylic acid or inorganic acid, various commonly known salts can be used. As the example of suitable salt, it is not particularly limited, and can be selected from sodium salt, potassium salt, ammonium salt, alkylammonium salt, amine salt listed below, one or more of amidine salts. As amine salt, primary amine, secondary amine, tertiary amine salt can be used, as an example, methylamine, ethylamine, dimethylamine, diethylamine, trimethylamine, triethylamine, ethyldimethylamine, diethylmethylamine, methanolamine, ethanolamine, dimethanolamine, diethanolamine, trimethanolamine, triethanolamine, pyrrolidinecarbonitrile, piperidine, piperazine, morpholine, methylmorpholine, ethylmorpholine, oxazolidine, thiomorpholine, thiazolidinemorpholine, methylmorpholine, ethylmorpholine, oxazolidine, thiomorpholine, thiazolidine salts such as morpholine. Examples of amidine salts include salts such as 1,3-dimethylimidazoline, 1,3-diethylimidazoline, 1,2,3-trimethylimidazoline, 1,2,3,4-tetramethylimidazoline, 1,3-dimethyl-2-ethylimidazoline, 1,2-dimethyl-3-ethylimidazoline, 1,2-dimethyl-3-ethylimidazoline, 1,2,3-triethylimidazoline, and 1,2,3,4-tetraethylimidazoline. Examples of amidine salts include tetraalkylammonium salts and imidazolium salts.

[0082] Furthermore, when an inorganic acid or a salt thereof is used as an electrolyte component, it can be expected that the freezing point of the electrolyte solution will be lowered, which can contribute to improving the low-temperature characteristics of the electrolyte solution.

[0083] Furthermore, by using such an electrolyte component such as an inorganic acid or a salt thereof in combination with the electrolyte component such as the above-mentioned carboxylic acid or a salt thereof, the life of the electrolytic capacitor 10 is significantly extended compared to the case where the carboxylic acid or a salt thereof is used alone.

[0084] In the electrolyte solution related to the present embodiment, the amount of electrolyte contained therein can be appropriately determined according to the characteristics required by the electrolyte solution, the type of solvent used, the type of electrolyte used, and other conditions. Generally speaking, for example, when a carboxylic acid or a salt thereof is used as an electrolyte, its amount is preferably about 3% to 30% by mass of the total mass of the electrolyte solution. When the amount of the above-mentioned electrolyte is less than 3% by mass, the desired conductivity cannot be fully ensured. If it exceeds 30% by mass, the effect gradually reaches saturation, and in addition, it becomes difficult to dissolve in the solvent.

[0085] In addition, usually, when an inorganic acid or its salt is used as an electrolyte, its amount is preferably about 0.1% to 15% by mass of the total mass of the electrolyte. When the amount of the above-mentioned electrolyte does not meet 0.1% by mass, it becomes difficult to fully ensure the desired conductivity. If it exceeds 15% by mass, the conductivity gradually reaches saturation, and it becomes difficult to dissolve in the solvent. When a carboxylic acid or its salt is used in combination with an inorganic acid or its salt, it can also be used in a range of about 0.1% to 15% by mass of the total mass of the electrolyte. However, as mentioned above, the amount of electrolyte can be appropriately determined according to the characteristics required by the electrolyte, the type of electrolyte used, and other conditions. For example, an oxygen-containing acid of phosphorus (phosphoric acid, phosphorous acid, hypophosphorous acid, etc.) brings about a long life of the electrolytic capacitor 10 by inhibiting the hydration reaction of the electrode foils 20 and 23, or an oxygen-containing acid of phosphorus or its salt if it contains at least 0.01% by mass of the total mass of the electrolyte, then the effect is exerted. Therefore, by combining a plurality of electrolyte components as needed and adjusting the amount of each electrolyte component, etc., it is possible to ensure desired conductivity and obtain desired characteristics.

[0086] Furthermore, in the electrolyte solution according to the present embodiment, additives such as (1) chelates, (2) sugars, (3) gluconic acid and / or gluconolactone, (4) nitro compounds, (5) polymer compounds, and (6) phosphates are preferably added as needed. These additives may be used alone or in any combination of two or more. Each additive is described below.

[0087] (1) Chelate

[0088] As the chelate, for example, ethylenediaminetetraacetic acid (EDTA), trans-1,2-diaminocyclohexane-N,N,N',N',N'-tetraacetic acid-hydrate (CyDTA), dihydroxyethylglycine (DHEG), ethylenediaminetetra(methylenephosphonic acid) (EDTPO), diethylenetriamine-N,N,N',N",N"-pentaacetic acid (DTPA), diaminopropanoltetraacetic acid (DPTA-OH), ethylenediaminediacetic acid (EDDA), ethylenediamine-N,N'-bis(methylenephosphonic acid) 1 / 2 hydrate (EDDPO), glycol ether diaminetetraacetic acid (GEDTA), hydroxyethylethylenediaminetriacetic acid (EDTA-OH), etc. can be used. The chelate is usually preferably added in the range of 0.01% to 3% by mass of the total mass of the electrolyte. This chelate complex can bring about effects such as extending the life of the electrolytic capacitor 10 based on the suppression of the hydration reaction of the aluminum (Al) electrode foils 20 and 23 in the low-impedance capacitor, improving the low-temperature characteristics of the electrolytic capacitor 10 (the solvent has a composition close to an antifreeze state, so the change in impedance at room temperature and low temperature becomes smaller), and improving corrosion resistance.

[0089] (2) Carbohydrates

[0090] As sugars, for example, monosaccharides such as glucose, fructose, xylose, galactose, ribose, mannose, arabinose, lyxose, allose, aldose, gulose, idestarose and their derivatives, sugar alcohols such as erythritol, xylitol, mannitol, maltose, sucrose, fructose, cellobiose, sucrose, agarose and their derivatives, trisaccharides such as maltotriose and their derivatives, starch, glycogen, alginic acid, agar, polysaccharides such as polymannose and their derivatives, etc. Sugars are usually preferably added in the range of 0.01% to 5% by mass of the total mass of the electrolyte. This sugar can bring about the effects of extending the life of the electrolytic capacitor 10 by protecting the electrode foils 20 and 23, extending the life of the electrolytic capacitor 10 by inhibiting the hydration reaction of the aluminum (Al) electrode foils 20 and 23 in the low-impedance capacitor, inhibiting the degradation of the specified electrolyte components (for example, inhibiting the decomposition and activation of carboxylic acids), and improving the low-temperature characteristics of the electrolytic capacitor 10 (the solvent is a composition close to the antifreeze state, so the impedance change at room temperature and low temperature becomes smaller). If this sugar is used together with boric acid or its derivatives, they form esters, thereby improving the solubility of the sugar. Therefore, the addition of a specified amount of sugar can be performed reliably, and they can be fully acted in the electrolyte. As a result, the electrolytic capacitor 10 can be stably and fully extended in life. At this time, boric acid or its derivatives can be added as an electrolyte component (solute component) in the electrolyte, or they can be added specifically for the purpose of reacting with sugars. On the other hand, as a sugar added together with boric acid or its derivatives, mannitol and the like are suitable. The addition ratio of boric acid or its derivative to sugar is preferably in the range of "boric acid or its derivative: sugar = 10:1 to 1:5". If the amount of sugar added is too large, it becomes easy to dissolve in the solvent.

[0091] (3) Gluconic acid and / or gluconolactone

[0092] The electrolyte solution according to the present embodiment may contain gluconic acid and / or gluconolactone alone or in combination as necessary. Such additives are usually preferably added in an amount of 0.01% to 5% by mass of the total mass of the electrolyte solution.

[0093] (4) Nitro compounds

[0094] The electrolyte solution involved in this embodiment may contain at least one nitro compound selected from nitrobenzene, nitrophenol (e.g., p-nitrophenol), nitrobenzoic acid (e.g., p-nitrobenzoic acid, dinitrobenzoic acid), nitroacetophenone (e.g., p-nitroacetophenone), nitrobenzyl ether, nitrobenzyl alcohol, nitroxylene and other aromatic nitro compounds as needed.

[0095] In the electrolyte of the present embodiment, when the nitro compound as described above is used, there is an effect of absorbing hydrogen generated in the electrode foils 20 and 23. In addition, when two or more nitro compounds are mixed and used, a more preferable effect can be expected compared to using the above nitro compounds alone. In addition, the nitro compound is usually preferably added and used in the range of 0.01 mass % to 5 mass % of the total mass of the electrolyte. If the amount of the nitro compound added is less than 0.01 mass %, the desired effect is basically not obtained. On the contrary, even if it is more than 5 mass %, no further improvement of the desired effect can be expected, and it is also considered that it may have an adverse effect on other characteristics depending on the situation.

[0096] When the use of the nitro compound is further described, when the nitro compound is used alone, the water content in the solvent used gradually increases, and there is a tendency for the absorption effect to decrease. In addition, this tendency to decrease the absorption effect becomes significant when the electrolyte is placed in a high temperature environment. However, the problems caused by the use of such a nitro compound alone can be eliminated by using two or more nitro compounds in combination.

[0097] (5) Polymer compounds

[0098] As the polymer compound, for example, water-soluble silicone, polyacrylic acid or its derivatives, polymethacrylic acid or its derivatives, polyacrylamide or its derivatives, polyglutamic acid or its derivatives, polyglycerol or its derivatives, polyethylene glycol or its derivatives, polypropylene glycol or its derivatives, polyvinyl alcohol or its derivatives, polyoxyethylene glycol or its derivatives, polyoxyalkylene compounds, polysiloxanes, silicon dioxide, etc. can be used. They can be used alone or in any combination of two or more. The total amount of addition is preferably in the range of 0.1% to 30% by mass of the total mass of the electrolyte. This polymer compound can bring about the improvement of the withstand voltage characteristics of the electrolytic capacitor 10, the extension of the life of the electrolytic capacitor 10, and other effects that are consistent with the effects of each polymer compound.

[0099] The molecular weight of the polymer compound can be widely used, ranging from a relatively low molecular weight (oligomer) to a high molecular weight, depending on the function of each polymer compound, solubility / dispersibility in a solvent, or desired effect.

[0100] (6) Phosphate

[0101] As the phosphate ester, for example, methyl phosphate, ethyl phosphate, dimethyl phosphate, diethyl phosphate, trimethyl phosphate, triethyl phosphate, etc. can be used. Similar to chelates, such phosphate esters can suppress the hydration reaction of electrode foils 20 and 23, thereby suppressing the degradation of electrode foils 20 and 23 and suppressing the generation of hydrogen, thereby achieving a longer life of electrolytic capacitor 10.

[0102] Furthermore, the electrolyte solution according to the present embodiment may contain additives commonly used in the field of electrolytic capacitors such as aluminum electrolytic capacitors in addition to the above-mentioned additives. Examples of suitable additives include silane coupling agents, polymer electrolytes, and colloidal silica.

[0103] The separators 24 and 25 of the present embodiment are not particularly limited, but preferably, naturally produced cellulose materials, such as Manila hemp and plant pulp, can be used as raw materials, and the raw pulp is manufactured through dust removal, cleaning, beating, papermaking, etc. In addition, woven fabrics, non-woven fabrics, sheets, films, etc. made of synthetic fibers such as rayon, nylon, polyester, polyvinyl compounds, aramid, propionic acid, and polyurethane can also be used. In addition, mixed products and blended products of natural fibers and synthetic fibers can also be used.

[0104] Here, in the sintered body foil, the path that reaches the depth of the pit (here, it refers to the pores formed in the sintered body) is long, and there is a concern that the high-viscosity electrolyte will not be sufficiently impregnated into the sintered body foil. For example, if a polymer compound or the like having a withstand voltage improvement effect is added to the electrolyte of the electrolytic capacitor 10 for high voltage, the electrolyte will become highly viscous due to the viscosity of the polymer compound or the like, and there is a concern that the penetration will become insufficient. Therefore, in the electrolytic capacitor 10 for high voltage, for example, it is preferred to pre-coat the separators 24 and 25 with an additive for the electrolyte such as a polymer compound having a withstand voltage improvement effect before making the capacitor element 1 (in this embodiment, winding). In this way, a low-viscosity electrolyte that is completely free of the additive or contains only a small amount of the additive can be formed, and a reduction in the impregnation property can be prevented.

[0105] In addition, since the sintered foil is prone to produce fine powder and burrs when slitting, these factors make the short circuit rate of the electrolytic capacitor 10 having the sintered foil relatively high. Therefore, in the electrolytic capacitor 10 of this embodiment, it is preferred to set the thickness of the separators 24 and 25 to a range of 20 μm to 150 μm and the density to 0.2 g / cm 3 ~1.0g / cm 3 Thus, the occurrence rate of short circuit can be reduced.

[0106] The capacitor element 1 of the present embodiment comprises: the anode foil 20 as a sintered body foil, the cathode foil 23 as an etched foil, and the separators 24 and 25 sandwiched between the anode foil 20 and the cathode foil 23 as described above. The manufacturing steps are as follows. First, the anode foil 20 formed into a sintered body and subjected to a chemical conversion process is cut into appropriate sizes. In addition, the cathode foil 23 subjected to an etching process is also cut into appropriate sizes. Then, the lead tabs 5 are respectively joined to the anode foil 20 and the cathode foil 23. The joining of the electrode foils 20 and 23 to the lead tabs 5 can be performed by known methods such as caulking, cold pressing, ultrasonic bonding, laser welding, etc. In caulking, in order to prevent the foil from breaking during joining, a through hole can be pre-formed at the joining portion of the electrode foils 20 and 23 before joining based on pressing. In the cold pressing, the mold in contact with the electrode foils 20 and 23 in the mold for the pressing can be coated with a high hardness and low friction material such as diamond-like carbon (DLC) and titanium carbide (TiC). In this way, the wear resistance of the mold can be ensured, and the adhesion and deposition of fine powder of the electrode foils 20 and 23 can be prevented.

[0107] Then, in the wound electrolytic capacitor 10, as Figure 2 As shown, the anode foil 20, the cathode foil 23 and the separators 24 and 25 are wound in a manner such that the anode foil 20 and the cathode foil 23 are divided by the first separator 24 or the second separator 25 to produce a capacitor element 1 (wherein, Figure 2 Lead 2 (lead tab 5 and terminal 6) are omitted). Then, the capacitor element 1 is immersed in the electrolyte, so that the electrolyte is impregnated into the capacitor element 1. The impregnation of the electrolyte can be carried out at normal pressure (atmospheric pressure), but it is more preferably carried out under reduced pressure. In this reduced pressure method, the capacitor element 1 is immersed in the electrolyte in a reduced pressure atmosphere, and after a constant time, the impregnation state is maintained unchanged and restored to the atmospheric pressure atmosphere, so that the electrolyte is impregnated. In addition, after returning to the atmospheric atmosphere, a pressurized atmosphere can be further formed while maintaining the impregnation state unchanged. The reduced pressure is preferably less than 1.5 kPa in absolute pressure, and the pressurization is preferably in the range of 0.15 MPa to 1.0 MPa in gauge pressure. It should be noted that by heating the electrolyte from reduced pressure to pressurization within the range allowed by the evaporation of the electrolyte components. If the electrolyte is heated, the viscosity of the electrolyte decreases, and therefore, the impregnation property can be improved.

[0108] Then, capacitor element 1 impregnated with the electrolyte is housed in exterior case 4. Then, the opening of exterior case 4 is sealed by sealing member 3, and the opening edge is fitted tightly. According to the above steps, electrolytic capacitor 10 can be manufactured. After that, an aging treatment can be performed as needed.

[0109] The lead 2 is led out from the lead through hole of the sealing body 3. The terminal 6 used as an external connection terminal or an external electrode terminal can be integrally formed with the lead tab 5, or can be connected to the lead tab 5 at an appropriate time during the manufacturing process of the electrolytic capacitor 10. The lead 2 (lead tab 5 and terminal 6) can be formed of various metal materials such as iron, copper, tin, lead, silver, gold, zinc, bismuth, tungsten, nickel, titanium, and chromium. For the purpose of reducing the ESR of the electrolytic capacitor 10, it is advantageous to form the lead 2 from a highly conductive metal material such as copper, silver, iron, and gold, and it is particularly advantageous to form it from copper or silver.

[0110] In addition, the lead tab 5, which is the connection part with the electrode foil 20, 23, is subjected to chemical conversion by generating a potential difference between it and the electrolyte in the same manner as the aforementioned etched foil (cathode foil 23) through repeated charging and discharging of the electrolytic capacitor 10. Therefore, for the purpose of suppressing the progress of chemical conversion during charging and discharging, etc., the lead tab 5 can be subjected to chemical conversion treatment to form a chemical conversion film (oxide film). Thus, the effect of reducing the leakage current is obtained. The chemical conversion treatment at this time is preferably phosphoric acid chemical conversion or adipic acid chemical conversion. Thus, the chemical conversion property can configure a good substance in the lead tab 5 and the electrode foil 20, 23, so that the film repair can be performed in a shorter time, and the increase of the leakage current can also be prevented when mechanical stress is applied.

[0111] In addition, when the chemical conversion of the lead pole tab 5 connected to the cathode foil 23 (etched foil) is performed by the repetition of charge and discharge of the electrolytic capacitor 10, there is a concern that the lead pole tab 5 and the anode foil 20 (sintered body foil) may cause a short circuit due to heat release due to charge and discharge. Therefore, in particular, the lead pole tab 5 connected to the cathode foil 23 may be etched and further chemically converted. Thus, by further suppressing the progress of the chemical conversion, a short circuit can be prevented. It should be noted that the lead pole tab 5 connected to the anode foil 20 may also be etched.

[0112] The outer casing 4 for housing the capacitor element 1 can be made of aluminum that is commonly used in the past. When strength is required, non-heat-treated aluminum with a purity of 99.0% or more (such as non-heat-treated aluminum 1100), heat-treated aluminum with a purity of 99.0% or more (such as H22 material of 1000 series aluminum), tuning materials of aluminum alloys containing manganese (Mn) and (or) magnesium (Mg) (such as O material of aluminum alloy 3003, 22 material of 3000 series aluminum alloy, O material of aluminum alloy 3004), etc. can be used.

[0113] Note that capacitor element 1 may be bonded to and housed in exterior case 4 by an adhesive. In this way, capacitor element 1 is fixed, and vibration resistance of electrolytic capacitor 10 can be improved. As the adhesive, a known adhesive may be used as appropriate.

[0114] The sealing body 3 used in the electrolytic capacitor 10 in the present embodiment can be formed of a variety of commonly used materials as long as the material has high hardness and moderate elasticity, is impermeable to the electrolyte, and has good airtightness as the sealing body 3. As suitable materials for the sealing body 3, elastic rubbers such as natural rubber (NR), styrene-butadiene rubber (SBR), ethylene-propylene dimer (EPT), and isobutylene-isoprene rubber (IIR) can be cited. In particular, isobutylene-isoprene rubber (IIR) has high airtightness and the electrolyte does not pass through as vapor, so it is suitable. In addition, it is further preferred to use IIR with better heat resistance, such as sulfur vulcanization, quinone vulcanization, resin vulcanization, peroxide vulcanization, etc.

[0115] Furthermore, in order to suppress mechanical stress, there is also a method of using a rubber material with higher hardness. As hardness, a sealing rubber having a rubber hardness measurement (30-second value) of 80 (IRHD / M) or more based on an IRHD hardness tester is used, so that mechanical stress is not easily applied, and the increase in leakage current can be suppressed.

[0116] Furthermore, a composite material of a resin material having airtightness and sufficient strength and an elastic rubber can be advantageously used to replace the above-mentioned sealing body 3 material. As the resin material, for example, fluororesins such as PTFE, polyphenylene sulfide (PPS), polyarylate (PAR), liquid crystal polymer, polysulfone (PSF), polyethersulfone, polyetheretherketone (PEEK), polyetherimide (PEI), polyamide (aromatic polyamide, aliphatic polyamide), polyimide (PI), polyamideimide (PAI), polycarbonate, polyacetal, phenolic resin, modified polyphenylene ether, etc. It should be noted that the sealing body 3 comprising two layers of resin material and rubber material is suitable for use in a self-supporting electrolytic capacitor of a substrate.

[0117] Example

[0118] Next, the present invention will be further described based on examples. The examples listed here are for illustrating the present invention and are not intended to limit the present invention. It should be noted that "%" in the table means "mass %".

[0119] Example 1

[0120] In this example, a wound aluminum electrolytic capacitor was manufactured according to the following steps.

[0121] The anode foil of the aluminum powder sintered body is produced by the manufacturing method disclosed above (the first step to the third step), and then the electrode lead wire is installed. In addition, another aluminum foil is electrochemically etched to produce a cathode foil, and then the electrode lead wire is installed. Then, a separator (separation paper) is clamped between the anode foil and the cathode foil and wound to produce a capacitor element. On the other hand, based on the composition table shown in Table 1 below, a solvent component and an electrolyte component are added in sequence in a constant container, and then stirred to dissolve and prepare an electrolyte solution.

[0122] After the capacitor element is impregnated with the electrolyte prepared by the above-mentioned preparation method, the electrode lead wires are housed in a bottomed aluminum case so as to protrude outside the case, and the opening of the case is sealed with an elastic sealing body, followed by aging treatment to produce an electrolytic capacitor with a wound structure.

[0123] Comparative Example 1

[0124] In Comparative Example 1, an aluminum foil was electrochemically etched and then anodized to form an oxide film on the surface, which was used as an anode foil. The other methods for preparing an electrolytic capacitor were the same as those described in Example 1.

[0125] In both Example 1 and Comparative Example 1, samples were produced so that the foil withstand voltage became equivalent to 400 WV in terms of capacitor withstand voltage.

[0126] Then, the electrostatic capacitance of the electrolytic capacitors prepared in Example 1 and Comparative Example 1 was measured at 25° C., a frequency of 120 Hz, and 10 kHz, and the measured values ​​described in the following Table 1 were obtained.

[0127] [Table 1]

[0128]

[0129] Comparing the electrostatic capacitance of the capacitors of Example 1 and Comparative Example 1, it is found that the electrostatic capacitance of the capacitors of Example 1 using the anode foil of the sintered aluminum powder is larger than that of Comparative Example 1 using the etched anode foil.

[0130] Embodiments 2 to 12

[0131] Next, for the capacitors made by the same method as in Example 1, the relationship between the resistivity of the electrolyte and the electrostatic capacitance of the capacitor is compared at an average powder particle size of 2.5 μm and 6 μm. The method for making the electrolytic capacitors of Examples 2 to 12 repeats the same method as in Example 1, and in the method for making the electrolyte, the components are made the same as in Example 1, and the composition is adjusted to make resistivities of 100 Ω·cm, 30°C to 2000 Ω·cm, 30°C, respectively. It should be noted that the samples made with an average powder particle size of 2.5 μm have a foil withstand voltage equivalent to 400 WV in a capacitor withstand voltage meter, and the samples made with an average powder particle size of 6 μm have a foil withstand voltage equivalent to 450 WV in a capacitor withstand voltage meter.

[0132] Comparative Examples 2 to 12

[0133] The method for preparing the capacitors of the aluminum etched foil used in Comparative Examples 2 to 12 was the same as that in Comparative Example 1, and the method for preparing the electrolyte was the same as that described in Examples 2 to 12. In the same manner as in Examples 2 to 12, samples with a foil withstand voltage equivalent to 400 WV and a foil withstand voltage equivalent to 450 WV were prepared in the capacitor withstand voltage meter.

[0134] Then, the electrostatic capacitance of the electrolytic capacitors prepared in Examples 1 to 12 and Comparative Examples 1 to 12 was measured at 25° C., a frequency of 120 Hz, and 10 kHz, and the measured values ​​described in the following Tables 2 and 3 were obtained.

[0135] [Table 2]

[0136] The average particle size of aluminum powder sintered body: 2.5 μm

[0137] The capacitor withstand voltage is equivalent to 400WV

[0138]

[0139] [Table 3]

[0140] Average particle size of aluminum powder sintered body: 6μm

[0141] In capacitor voltage, equivalent to 450WV

[0142]

[0143] Tables 2 and 3 show the electrostatic capacitance at 120 Hz and 10 kHz. As a representative use of capacitors, they are used for primary-side smoothing of switching power supplies. In addition to smoothing the input voltage from the commercial power line, they also have the function of absorbing current noise from components such as MOS-FETs that repeatedly switch at a frequency of around 10 kHz in the later stage of the circuit. This noise is called EMI, and it has an adverse effect on other electrical equipment through the commercial power line, so it is subject to regulation according to the EMC Directive (89 / 336 / EEC). In order to help reduce this noise, it is important to increase the electrostatic capacitance around 10 kHz. When the "ratio" of the electrostatic capacitance at 120 Hz and 10 kHz is recorded here, it is compared with the electrostatic capacitance at 10 kHz itself. The electrolytic capacitor using the aluminum powder sintered body foil with a large foil capacitance will naturally become a value larger than the electrolytic capacitor using the etched foil. Therefore, by recording the "ratio", it is usually used to compare the ease of generating the 10 kHz electrostatic capacitance relative to the electrostatic capacitance limited at 120 Hz.

[0144] If the ratio of the electrostatic capacitance at 120Hz and 10kHz recorded in Tables 2 and 3 is observed, when the electrolyte resistivity is 100Ω·cm to 1500Ω·cm, the aluminum powder sintered body foil shows a value higher than the etched foil. At 2000Ω·cm, the powder sintered body foil shows a value lower than the etched foil, but it is believed that this is because the structure of the aluminum powder sintered body foil is formed by the aggregation of particles rather than the tunnel-shaped etching pits seen in the previous etching foil, until the passage deep in the pit is longer, so it becomes difficult to generate capacitance at high frequencies when using a high-resistivity electrolyte. That is, in an aluminum electrolytic capacitor, if the aluminum powder sintered body foil is combined with an electrolyte with a resistivity of less than 1500Ω·cm, it is easier to generate a 10kHz capacity relative to the 120Hz capacity compared to the aluminum etching foil used in the past.

[0145] Embodiment 13, 14

[0146] Next, the correlation between the purity of the aluminum substrate and the life of the capacitor was compared.

[0147] The electrolytic capacitor of Example 13 was produced using an aluminum powder sintered foil having an aluminum purity of 99.99 wt % or more in the base material and an aluminum purity of 99.99 wt % or more in the powder. The capacitor production method otherwise repeated the method described in Example 1.

[0148] In addition, the electrolytic capacitor of Example 14 is produced using an aluminum powder sintered foil whose aluminum purity of the base material is 99.8 wt % or more and less than 99.95 wt % and whose aluminum purity of the powder is 99.99 wt % or more. The capacitor production method otherwise repeats the method described in Example 1.

[0149] Then, the electrolytic capacitors of Examples 13 and 14 were subjected to a high temperature load test at 425 V and 105° C. Figure 3 The leakage current value of the electrolytic capacitor in the high temperature load test is shown. The leakage current of the capacitor of any embodiment is suppressed to less than 12μA, but in particular, in the capacitor with a substrate purity of 99.99% by weight or more (Example 13), there is no tendency for the leakage current to increase after 3000 hours and thereafter, and the increase in leakage current is suppressed. The increase in leakage current leads to an increase in the amount of gas generated inside the capacitor, and the internal pressure rises slowly, which increases the risk of valve operation at an early stage. Therefore, in order to form good life characteristics, it is more preferred that the aluminum purity of the substrate is 99.99% by weight or more. In addition, for the aluminum powder electrically bonded to the substrate, it is also understood that the aluminum purity is preferably 99.99% by weight or more for the same reason.

[0150] It should be noted that in this specification, the "average particle size (D50)" refers to the particle size at 50% of the cumulative value in the volume-based particle size distribution determined by the laser diffraction / scattering method in the case of powder, and the particle size at 50% of the cumulative value in the volume-based particle size distribution of the sintered particles on the surface or cross-section of the sintered body measured by observation based on a scanning electron microscope in the case of sintered particles. The diameter of the observed sintered particles is measured as the particle size. Among them, the sintered particles are sometimes in a state where the powder particles after sintering are melted and the shape is partially collapsed, or the powder particles after sintering are partially connected to each other. In this case, the portion with a roughly circular shape is approximately regarded as a sintered particle, and its maximum diameter is measured as the particle size. On the other hand, the portion where it is difficult to distinguish a roughly circular shape is excluded. The particle size of a specified number of sintered particles is measured, and the volume-based particle size distribution is calculated from these number-based particle size distributions. Then, the particle size at 50% of the cumulative value in the particle size distribution is obtained as the average particle size (D50) of the sintered particles. It should be noted that the particle size of the powder particles does not change substantially before and after sintering, and the average particle size (D50) of the powder determined by the above method is substantially the same as the average particle size (D50) of the sintered particles of the powder.

Claims

1. An electrolytic capacitor, characterized in that: A capacitor element and an electrolyte are provided, wherein the capacitor element includes an anode foil, a cathode foil, and a separator interposed between the anode foil and the cathode foil, and the electrolyte is impregnated in the capacitor element. The anode foil or the cathode foil has a sintered body composed of sintered particles containing powder of at least one of aluminum and an aluminum alloy. The resistivity of the electrolyte is less than 1500 Ω·cm, The average particle size (D50) of the powder or the sintered particles is 6 μm or less.

2. The electrolytic capacitor according to claim 1, characterized in that: The anode foil or the cathode foil includes the sintered body and a substrate for supporting the sintered body.

3. The electrolytic capacitor according to claim 1 or 2, characterized in that: The electrolyte contains: a solvent comprising an organic solvent, or a solvent comprising a mixture of water and an organic solvent; and, At least one electrolyte selected from the group consisting of an organic acid or an organic acid salt, an inorganic acid or an inorganic acid salt, and a mixture of an organic acid or an organic acid salt and an inorganic acid or an inorganic acid salt.

Citation Information

Patent Citations

  • The sintered-type electrolytic capacitor

    JP1984140430U

  • Aluminum electrolytic capacitor

    JP1990267916A

  • Electrolytic capacitor

    JP2006108159A

  • Electrode material for aluminum electrolytic capacitor, and method for producing same

    CN103688327A

  • Method for manufacturing electrode material for aluminum electrolytic capacitor

    CN104094370A